Evaluation of the eating habits of Polish esports players using the Quick Dietary Survey (QDS) - Szot, M.; Fraczek, B. (Journal of Kinesiology and Exercise Sciences, 2024)
Background: Proper diet is crucial for the health and physical fitness for both traditional sport and esport. The study aimed to evaluate eating behaviours of elitePolish esports players using the QDS questionnaire.